Mortality among Alaska Native Adults with Confirmed Hepatitis C Virus Infection Compared with the General Population in Alaska, 1995–2016 - Sara S. Bressler; Dana Bruden; Leisha D. Nolen; Michael G. Bruce; Lisa Towshend-Bulson; Philip Spradling; Brian J. McMahon (Canadian Journal of Gastroenterology and Hepatology)
Background. Hepatitis C virus (HCV) infection incidence rates in the United States have increased since 2010 as a byproduct of the opioid crisis despite the introduction of direct-acting antiviral agents in 2013. HCV infection is associated with higher rates of liver-related and nonhepatic causes of death. Methods. This study compared demographic characteristics and age-adjusted death rates from 1995 to 2016 among Alaska Native (AN) adults infected with HCV (AK-HepC) to rates among the AN and non-AN adult populations living in Alaska. Liver-related disease (LRD) and other disease-specific age-adjusted death rates were compared between the populations. Results. The all-cause death rate among the AK-HepC cohort was 2.2- and 3.4-fold higher than AN and non-AN adults, respectively, and remained stable over time in all populations. The LRD death rate among the AK-HepC cohort was 18- and 11-fold higher than the non-AN and AN, respectively. The liver cancer rate among the AK-HepC cohort was 26-fold higher compared to the Alaska statewide population. The AK-HepC cohort had elevated rates of death associated with nonhepatic diseases with circulatory disease having the highest rate in all populations. Among liver cancer deaths in the AK-HepC cohort, 32% had HCV listed as a contributing cause of death on the death certificate. Conclusions. Death rates in the AK-HepC cohort remained stable since 1995 and higher compared to the general population. People with HCV infection had an elevated risk for all-cause, liver-related, and nonhepatic causes of death. Hepatitis C infection may be underrepresented as a cause of mortality in the United States.